2013
DOI: 10.5489/cuaj.1245
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer-specific survival differences in patients treated by radical prostatectomy versus curative radiotherapy

Abstract: E299Cite as: Can Urol Assoc J 2013;7(5-6):e299-305. http://dx.doi.org/10.5489/cuaj.11294 Published online May 13, 2013 (early released July 16, 2012). AbstractObjective: We compared the cause-specific survival of patients who received radiotherapy to those who received surgery for cure of their prostate cancer using a number of design and analytic steps to mitigate confounding by indication. Methods: This was a case-cohort study of 2213 patients in the Ontario Cancer Registry diagnosed between 1990 and 1998 wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Few randomised clinical trials have compared outcomes between radical prostatectomy and radiotherapy. One trial suggested that, for low/intermediate-risk tumours, radiotherapy and radical prostatectomy offer similar biochemical disease-free survival, but that radiotherapy is more effective than surgery for those with high-risk disease (Aizer et al , 2009) findings corroborated by a population-based study (DeGroot et al , 2012). Two other population-based studies have suggested that patients with high-risk disease and without comorbidity benefit more from surgery than radiotherapy (Ladjevardi et al , 2010; Abdollah et al , 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Few randomised clinical trials have compared outcomes between radical prostatectomy and radiotherapy. One trial suggested that, for low/intermediate-risk tumours, radiotherapy and radical prostatectomy offer similar biochemical disease-free survival, but that radiotherapy is more effective than surgery for those with high-risk disease (Aizer et al , 2009) findings corroborated by a population-based study (DeGroot et al , 2012). Two other population-based studies have suggested that patients with high-risk disease and without comorbidity benefit more from surgery than radiotherapy (Ladjevardi et al , 2010; Abdollah et al , 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, the NCCN guidelines were amended, removing the option of AS for those with intermediate risk PC . Up to 12‐year survival rates are similar for men with LPC randomised to either observation or RP , and RP and radiotherapy survival outcomes are also similar . Despite this, estimated AS uptake rates for men with LPC are 10% and 42% in American and Australian men, respectively.…”
Section: Introductionmentioning
confidence: 92%
“…After removing the duplicates, we identified 2,334 records from the initial title and abstract screening process, retrieved and reviewed 74 articles in full‐text assessment for eligibility, among which 52 were excluded based on the following reasons: no original articles ( n = 4), not population of interest ( n = 7), 100 or fewer participants ( n = 6), no outcome of interest ( n = 22), insufficient data ( n = 6), studies focused only on high‐risk or intermediate‐risk prostate cancer ( n = 7). Finally, 22 RCTs and retrospective articles (Abdollah et al., 2012; Aizer et al., 2009; Albertsen et al., 2007; Arvold et al., 2011; Bill‐Axelson et al., 2014; Colberg et al., 2007; Degroot et al., 2013; Fosså et al., 2014; Giberti et al., 2009; Hamdy et al., 2016; Hayashi et al., 2019; Hoffman et al., 2013; Ladjevardi et al., 2010; Merglen et al., 2007; Merino et al., 2013; Patrick & Walsh, 2005; Resnick et al., 2013; Rice et al., 2013; Stattin et al., 2010; Taguchi et al., 2015; Tward et al., 2010; Wong et al., 2006) were included in our NMA with a total of 185,363 patients treated by at least one of the three treatment strategies. Sixteen trials (Aizer et al., 2009; Albertsen et al., 2007; Arvold et al., 2011; Degroot et al., 2013; Fosså et al., 2014; Giberti et al., 2009; Hamdy et al., 2016; Hayashi et al., 2019; Ladjevardi et al., 2010; Merglen et al., 2007; Merino et al., 2013; Patrick & Walsh, 2005; Resnick et al., 2013; Rice et al., 2013; Stattin et al., 2010; Taguchi et al., 2015) investigated RP versus RT, whereas 11 trials (Abdollah et al., 2012; Albertsen et al., 2007; Bill‐Axelson et al., 2014; Fosså et al., 2014; Hamdy et al., 2016; Ladjevardi et al., 2010; Merglen et al., 2007; Stattin et al., 2010; ...…”
Section: Resultsmentioning
confidence: 99%